2021
DOI: 10.3390/neurolint13010001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Music Intervention on Dementia: A Review Using Meta-Narrative Method and Agenda for Future Research

Abstract: Background: Dementia, a significant cognitive impairment, is characterized by a decline in memory. It affects an individual’s mood and behavior, which can impair their quality of life and well-being. Studies show that the demand for applying music as a new therapy method for dementia has increased during the last decades. Objective: To review the studies conducted on the impacts of music on different symptoms of dementia and provide readers with a more detailed picture of the efficacy of music, and recognize g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 71 publications
1
17
0
1
Order By: Relevance
“…El Haj et al [14] stated that the use of personally meaningful music allows autobiographical memories to be evoked with higher fluency and expressed with higher grammatical complexity [5]. Our findings with regard to the impact that music has on communication coincides with previous studies that suggest people with dementia can benefit from music, and that it can improve language skills, verbal and non-verbal expressions, uninhibited self-expression, cognitive abilities, and sociability [20]. Although most of the variables suggest an improvement in the performance of AM in older adults with Alzheimer's disease, in the episodic component of the Autobiographical Memory Interview, no significant difference was observed.…”
Section: -Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…El Haj et al [14] stated that the use of personally meaningful music allows autobiographical memories to be evoked with higher fluency and expressed with higher grammatical complexity [5]. Our findings with regard to the impact that music has on communication coincides with previous studies that suggest people with dementia can benefit from music, and that it can improve language skills, verbal and non-verbal expressions, uninhibited self-expression, cognitive abilities, and sociability [20]. Although most of the variables suggest an improvement in the performance of AM in older adults with Alzheimer's disease, in the episodic component of the Autobiographical Memory Interview, no significant difference was observed.…”
Section: -Discussionsupporting
confidence: 87%
“…In addition, through musical training, neuroplasticity is stimulated, and neuronal degeneration is reduced. Authors such as Soufineyestani, Khan, and Sufineyestani [20] suggest that singing can improve mood, reduce behavioral disturbances, optimize the functioning of cognitive abilities, and increase hormone levels and heartbeat. Playing an instrument can prevent or delay the onset of symptoms.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative benefit of Receptive Music Therapy (RMT) in patients with dementia has been well described elsewhere. 31 , 32 , 38 , 39 This project aimed to provide quantitative evidence of the age in healthy individuals when popular music was best recalled, thereby demonstrating an era for the reminiscence bump. This era could then be sampled to create personalized playlists for RMT in people living with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that they utilize this approach to obtain a sense of control over their lives more than to be as effective as before. The Table 1 shows the different stages of dementia and how each stage affects PwD in their daily lives (Soufineyestani et al, 2021). As the quality of life for people in most developed countries increases due to health care and medicine being very much advanced nowadays, it does not guarantee that elderly people will not be affected by any illnesses that are common with their age .…”
Section: Related Workmentioning
confidence: 99%